2017
DOI: 10.1002/asi.23878
|View full text |Cite
|
Sign up to set email alerts
|

A combined fuzzy‐SEM evaluation approach to identify the key drivers of the academic library service quality in the digital technology era: An empirical study

Abstract: A conceptual model of the Academic Library (AL) service quality is hypothesized in the present article, and then validated and analyzed by a novel evaluation approach. Specifically, the conceptual model integrates the fundamental attributes of the canonical AL service together with those more relevant of the new and widely considered AL Electronic Service (e‐services). As concerns the evaluation approach, it incorporates the Fuzzy Sets Theory (FST) so as to deal with the students' uncertainty over their own ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, no bibliometric study has been conducted on LSQ so far. There have been various empirical studies conducted solely on LSQ, including those by Wu et al (2019) on improving LSQ from the perspective of big data; Hossain (2020) on user satisfaction and LSQ; Kumar and Mahajan (2019a) on evaluating LSQ of the University of Kashmir; Choshaly and Mirabolghasemi (2019) on assessing users satisfaction of LSQ; Gathoni and Van der Walt (2019) on evaluating LSQ from TQM approach; Mallya and Payini (2019) on an evaluation of students' perceptions of LSQ; Long et al (2019) on measuring users' satisfaction with university LSQ; Griadhi et al (2018) on the effect of LSQ on motivation and learning achievement; Jackson (2017) on measuring of university rankings through LSQ; and an empirical study by La Fata and Lupo (2017) to identify the key drivers of the academic LSQ in the digital technology era, etc. Hence, by conducting a bibliometric analysis on LSQ, this study is an attempt to fill the gap in the literature.…”
Section: Global Research On Library Service Qualitymentioning
confidence: 99%
“…However, no bibliometric study has been conducted on LSQ so far. There have been various empirical studies conducted solely on LSQ, including those by Wu et al (2019) on improving LSQ from the perspective of big data; Hossain (2020) on user satisfaction and LSQ; Kumar and Mahajan (2019a) on evaluating LSQ of the University of Kashmir; Choshaly and Mirabolghasemi (2019) on assessing users satisfaction of LSQ; Gathoni and Van der Walt (2019) on evaluating LSQ from TQM approach; Mallya and Payini (2019) on an evaluation of students' perceptions of LSQ; Long et al (2019) on measuring users' satisfaction with university LSQ; Griadhi et al (2018) on the effect of LSQ on motivation and learning achievement; Jackson (2017) on measuring of university rankings through LSQ; and an empirical study by La Fata and Lupo (2017) to identify the key drivers of the academic LSQ in the digital technology era, etc. Hence, by conducting a bibliometric analysis on LSQ, this study is an attempt to fill the gap in the literature.…”
Section: Global Research On Library Service Qualitymentioning
confidence: 99%
“…Four studies indicated the sub category of 'library environment' as one of the dimensions (Afthanorhan et al, 2019;Mohindra and Kumar, 2015;Xi et al, 2018), identified 25 failure items, which need to improve the quality of services by converting the verbal expressions in the intuitionistic fuzzy environment (Tooranloo et al, 2018). Interestingly, 'library staff' has remained in the focus by five different studies, which indicate that staff plays the vital role to connect library services with the users' needs (Bae and Cha, 2015;Dash and Padhi, 2016;Manuela La Fata and Lupo, 2017;Mat Dahan et al, 2016;Mohindra and Kumar, 2015).…”
Section: Emerging Patterns and Trends Reflected On Lsq Studiesmentioning
confidence: 99%
“…Regarding the sub-categories of user perception, there are various instances where the user perception was examined and explored on different samples from various libraries across the globe. Users' viewpoints/judgements/perceptions or their open-comments recorded through LibQUAL+ tool were explored to determine the service quality of libraries (Cabrerizo et al, 2017;De Jager, 2015;Guder, 2017;Kumar and Mahajan, 2019b;Luther, 2015;McCaffrey and Breen, 2016;Manuela La Fata and Lupo, 2017;Moore, 2017;Natesan et al, 2015;Sullo, 2019). Besides examining user perceptions through LibQUAL+ studies, researchers found evidence of ServQUAL studies too where the perceptions of library users were analysed by adopting TQM methodology and DEMATEL technique (Chen, 2016;Gathoni and Van der Walt, 2019).…”
Section: Emerging Patterns and Trends Reflected On Lsq Studiesmentioning
confidence: 99%
“…eir development involves numerous factors [11][12][13]. To complement government fiscal investment, Siregar and Dewiyana [14] optimized the public cultural service system, built up a public-private partnership (PPP) service supply model for libraries, and analyzed the intrinsic logic of introducing the model.…”
Section: Introductionmentioning
confidence: 99%